Preparation and characterization of two supramolecular complexes with 5-amino-2,4,6-triiodoisophthalic acid under N-donor auxiliary ligand intervention - Zhang, Kou-Lin; Chang, Yan; Ng, Seik Weng (Elsevier, 2011)
Assemblies of 5-amino-2,4,6-triiodoisophthalic acid (H2ATIBDC) with Cd(II) and Zn(II) in the presence of N-donor auxiliary ligand, 1,4-bis(1,2,4-triazol-1-yl)butane (btb), at ambient conditions yield two new supramolecular complexes, [Cd(ATIBDC)(btb)(H2O)2] ·3H2O (1), and [Zn(ATIBDC)(btb)]·2H2O (2). Generally, these two complexes display 1D ATIBDC2--bridged coordination arrays. Distinct extended 3D network architectures are further constructed with the help of weak secondary interactions especially aromatic stacking, halogen bonding, and hydrogen bonding as supramolecular driving forces. It is worthy to mention that halogen bonds (C-I⋯π and C-I⋯N/O) play important roles in the supramolecular assembly. The pentameric cluster (H2O)5 in 1 assembles into highly ordered helical infinite chains. Complex 2 exhibits the fascinating single-walled tube-like chain structure. It loses crystallinity rapidly in the air and leads to the formation of [Zn(ATIBDC)(btb)]·H2O (2A). Thermal stabilities and solid state fluorescent properties of complexes 1 and 2A have been studied. © 2010 Elsevier B.V. All rights reserved.